Економічний механізм рекурсивної співпраці лісових господарств та територіальних громад щодо ефективного використання дикоросів - Пасічник, Ю.В. (Вісник економічної науки України, 2022)
Виконано аналіз стану використання дикоросів в Україні порівняно з окремими країнами Європи та виявлено причини значного відставання українських виробників. Виявлено значні резерви щодо суттєвого збільшення обсягів заготівель дикоросів протягом перспективного періоду. Обґрунтовано механізм рекурсивної співпраці між лісогосподарськими структурами та територіальними громадами та запропоновано конкретні напрямки співробітництва між ними. It was emphasized that the forest industry plays an important role in economic, recreational, and ecological terms. The study focuses on current and potential opportunities for growing, collecting and using wild plants. Several aspects of the economic analysis of the state of the forest industry of Ukraine in comparison with the relevant indicators of individual European countries are presented. When comparing the level of forested areas, it was found that Ukraine occupies an average position. When comparing the amount of wild rose from one hectare, it was determined that Ukraine is ten times inferior to such countries as Portugal and the Czech Republic. Substantial reserves for a significant increase in the volume of wild rose harvesting during the prospective period have been substantiated. Significant problems of the current development of the forest industry were also revealed, in particular: insufficient theoretical support for the development of the forest industry, incompleteness of the processes of reforming the industry, ineffectiveness of the recursive cooperation of these farms and territorial communities, insufficient investment resources, in particular those that provide deep technological processing of raw materials. The analysis of the pragmatics of the functioning of forestry made it possible to come to a conclusion about promising productions, in particular, the use of wild berries in fresh form, freezing of products, drying of berries, fruits, mushrooms, canning, use in the confectionery and perfume industries, for medicinal purposes. The scientific novelty of the study is the development of an appropriate mechanism of cooperation between forestry and territorial communities, which is built on a recursive approach. The formation of this mechanism took into account the peculiarities of the development of communities as a result of decentralization and the directions of reforming the forest industry in the context of the European development vector of Ukraine. Taking into account the expediency of establishing such cooperation between these subjects, specific directions of cooperation between them are proposed, which include the coordination of the boundaries of the accompanying territorial areas, the audit of the volume of wild rose collection, the development of measures to increase the volume of wild rose collection, the assessment of the location for the possible processing of wild rose, the development of a joint business plan for collection and processing of wild plants. The mechanism of recursive cooperation between forestry structures and territorial communities is substantiated, and specific areas of cooperation between them are proposed.